A pilot study into the perception of unreliability of travel times using in-depth interviews - Yin-yen Tseng; Erik Verhoef; Gerard de Jong; Marco Kouwenhoven; Toon van der Hoorn (Journal of Choice Modelling, 2009)
Transport investments normally reduce travel times, but may also reduce unreliability. Conventional time gains can be evaluated in cost benefit analysis using standard values of time. For valuing reliability gains, however, no standard measures are readily available. The Dutch Ministry of Transport has commissioned a project to design a Stated Preference methodology. Reliability is a complex academic concept and it may be difficult to present and explain it to respondents. Therefore, a pilot study using in-depth face-to-face interviews has been carried out, in which various SP choice designs have been presented to the participants to test their understanding of the questions. In the end, we found a best design. But still, much care is needed for an acceptable response rate and to prevent illogical and inconsistent responses.
Keywords: 330; travel time unreliability; perception; stated preference design; value of reliability